Sistem Monitoring Multiruang Lokasi Lansia dengan Teknologi Indoor Positioning System (IPS) berbasis Wi-Fi dan Algoritma Random Forest - Dading Firwandhi Sukma; Dahnial Syauqy; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Elderly is a person aged more than or equal to 55 years. The elderly experience aging in their bodies which makes them vulnerable when they fall so that the elderly need intensive supervision to stay safe. In this study, a system was built that can monitor the elderly in six different rooms using Wi-Fi as an indicator of the Indoor Positioning System (IPS) technology.The system is built in two stages, namely the training stage and the testing stage. At the training stage, the system scans the Received Signal Strength Indication (RSSI) value from each room. From the data obtained, using the Random Forest Algorithm, a model is made that will be used on the microcontroller to predict the location of the elderly based on the scanned RSSI. In the testing phase, a wearable device was built that was attached to the waist of the elderly. Wearable devices will predict the position of the elderly and will send the prediction results to the database and displayed on the smartphone application. Tests are carried out to test the accuracy of the system that has been built. The results of the test obtained an average accuracy of all rooms of 82.85%.